Development of Authentic Assessment Based on Creative Thinking Skills in A Carbohydrates Qualitative Analysis Project-Based using Local Material - sari, Diah kartika; Sufiana, Jejem Mujamil; Wancik, K. Anom; Haryani, Maefa Eka (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2021)
Laboratory activities can improve creative thinking skills. This study aims to develop an authentic assessment based on creative thinking skills. This research is development research with the Rowntree development model. The research stages consist of the planning stage, the development stage and the evaluation stage. Data were analyzed using CVR and test description. This study was conducted with 33 participants. This research has produced an authentic assessment instrument consisting of learning indicators, written tests, test rubrics, product rubrics and psychomotor assessment rubrics. An authentic assessment developed in the qualitative analysis of carbohydrates with a CVR value obtained is +0.70, which can be considered valid for all validated components. The authentic assessment reliability test resulted in an average score of 56.56, a standard deviation of 25.06, and test reliability of 0.82. from the analysis, it was determined that the authentic assessment based on creative thinking skills of qualitative analysis of carbohydrates with local material developed had met the valid and reliable criteria.Â